CRISPR and RNAi systems : nanobiotechnology approaches to plant breeding and protection - Abd-Elsalam, Kamel A.; Lim, Ki-Taek (Nanobiotechnology for plant protection, 2021)
CRISPR and RNAi Systems: Nanobiotechnology Approaches to Plant Breeding and Protection presents a complete understanding of the RNAi and CRISPR/Cas9 techniques for controlling mycotoxins, fighting plant nematodes, and detecting plant pathogens. CRISPR/Cas genome editing enables efficient targeted modification in most crops, thus promising to accelerate crop improvement. CRISPR/Cas9 can be used for management of plant insects, and various plant pathogens. The book is an important reference source for both plant scientists and environmental scientists who want to understand how nano biotechnologically based approaches are being used to create more efficient plant protection and plant breeding systems.